72.5k views
1 vote
Find the fifth term of an=(-1)^n/2n-1

a.-1/7 b.-1/9 c.1/9 d.1/7

User Yevgeny
by
5.9k points

2 Answers

7 votes

Answer:

B

Explanation:

right on edge 2021

User Carl Suster
by
5.4k points
2 votes

Answer:

b) -1/9

Explanation:

Given


a_(n) = ((-1)^(n) )/(2n-1)

First term


a_(1) = ((-1)^(1) )/(2(1)-1) = -1

second term


a_(2) = ((-1)^(2) )/(2(2)-1) = (1)/(3)

Third term


a_(3) = ((-1)^(3) )/(2(3)-1) = (-1)/(5)

Fourth term


a_(4) = ((-1)^(4) )/(2(4)-1) = (1)/(7)

Fifth term


a_(5) = ((-1)^(5) )/(2(5)-1) = (-1)/(9)

User WebStylePress
by
5.5k points